Republic of Congo : Poverty Reduction Strategy Paper; Annual Progress Report. (IMF Staff Country Reports; Country Report, 2010)
This paper reviews the first annual progress report (APR) on implementation of the Poverty Reduction Strategy (PRS) in the Republic of Congo. The paper discusses that a number of stages in PRS implementation have already been completed. The PRS is being implemented in an international economic context marked by a severe economic and financial crisis. At the national level, favorable circumstances have enabled Congo to maintain a high level of economic growth averaging nearly 6 percent a year from 2005 to 2009.